The Effect of Motivation and Learning Activity on the Learning Achievement of Management Study Program Students Batch 2023 Semester 4 Class A & B STIE Yapan Surabaya City - Ulrianus Aristo Ngamal; Rohmah Kurniawati (International Journal of Multidisciplinary Sciences and Arts, 2025)
This study aims to determine, 1. the effect of learning motivation on the learning achievement of management students in batch 2023 semester 4 classes A and B at STIE YAPAN Surabaya city; 2. the effect of learning activeness on the learning achievement of management students in batch 2023 semester 4 classes A and B at STIE YAPAN Surabaya city; 3. the effect of learning motivation and learning activeness together to achieve management learning achievement in batch 2023 semester 4 classes A and B at STE YAPAN Surabaya city. This type of research uses descriptive qualitative with questionnaire / questionnaire data collection techniques. Before the questionnaire research was carried out, the validity and reliability tests were carried out using the help of the SPSS application with a total research population of 44 students. After collecting the data, the classical assumption test was carried out. From the results of data analysis, it can be seen that the coefficient of determination (R2) is 0.468 or 46.8%. Thus the contribution made by learning motivation and learning activeness to student achievement is 46.8%, while the remaining 53.2% is explained by other variables not revealed in this study. From the results of this research it can be concluded that, there is an influence of motivation and learning activeness on student achievement, where the higher the motivation and activeness of student learning, the more the student's learning achievement will increase.